KUALITAS PELAYANAN DINAS PERHUBUNGAN DALAM MEWUJUDKAN KESELAMATAN TRASPORTASI LAUT DI PELABUHAN LASALIMU KABUPATEN BUTON - La Manguntara; Hasniah (Journal Publicuho, 2023)
The purpose of this study was to describe the service quality of the Department of Transportation in realizing the safety of sea transportation and the factors that influence it at Lasalimu port, Buton Regency.  Data collection techniques used in this study were observation, interviews and documentation. The data that has been collected is then analyzed using descriptive qualitative data analysis techniques. The results showed that the service quality of the Department of Transportation in realizing the safety of sea transportation at Lasalimu port, Buton Regency, can be seen from several indicators, namely reliability, responsiveness, confidence, empathy and tangible.  All of these indicators show that the service quality of the transportation service in this case has been going well.  This situation is influenced by human factors, technical factors and weather factors.  In terms of human factors as service providers, although many employees have honorary status, quantitatively this is not a limiting factor in providing good service in realizing the safety of sea transportation.  Technically, employees who work in transportation services at the Lasalimu port have carried out their duties properly.  Meanwhile, regarding the weather factor, the Department of Transportation is really paying attention to this.  In circumstances where the weather does not support the safety of the voyage, this information is immediately conveyed to the captain to continue or postpone the voyage